2007
DOI: 10.1007/s11524-006-9154-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Vulnerability to Dengue in a Brazilian Urban Area During a 7-Year Surveillance

Abstract: This study considers the vulnerability of the urban area of the City of Belo Horizonte to dengue. A total number of 89,607 cases registered in the surveillance system from 1996 to 2002 were analyzed. Seven epidemic waves were identified during this period. Cases were grouped into 2,563 census areas, and three risk categories were proposed based on how many times each area reached a threshold established for each epidemic wave. The association between the risk categories and the socioeconomic, demographic and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
1
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 14 publications
4
66
1
9
Order By: Relevance
“…Recent studies have revealed that all dengue epidemics in China are caused by imported dengue cases [9][10][11]. In addition to the direct role of imported cases, the epidemics are also attributed to natural factors that affect the breeding and survival of the Aedes mosquitoes, such as climatic (temperature, humidity), vegetative, and socio-economic factors that affect human-mosquito contact, such as population density, population mobility, economic development, and living conditions of a specific city [7,[12][13][14]. These studies provide strong support for the necessity of appropriate prevention and control measures against dengue in China.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that all dengue epidemics in China are caused by imported dengue cases [9][10][11]. In addition to the direct role of imported cases, the epidemics are also attributed to natural factors that affect the breeding and survival of the Aedes mosquitoes, such as climatic (temperature, humidity), vegetative, and socio-economic factors that affect human-mosquito contact, such as population density, population mobility, economic development, and living conditions of a specific city [7,[12][13][14]. These studies provide strong support for the necessity of appropriate prevention and control measures against dengue in China.…”
Section: Introductionmentioning
confidence: 99%
“…Cependant si ces facteurs influencent potentiellement le cycle de contamination, ils ne sont pas systéma-tiquement identifiés comme tels, car le résultat des causalités non linéaires entre ces facteurs dépend des contextes locaux. La connaissance de ces relations permet malgré tout la mise en oeuvre d'actions à différentes échelles pour tenter d'améliorer les conditions de santé publique : contrôle régulier des gîtes en eau (Abe et al, 2005), mesures de protection intra domiciliaires (Singh et al, 2011), amélioration des conditions d'accès à l'eau des populations (Schmidt et al, 2011), interventions selon les types d'usages du sol (Thammapalo et al, 2008) ou encore politiques de planification urbaine (De Mattos Almeida et al, 2007).…”
Section: L'environnementunclassified
“…Les zones de concentration des indices vectoriels en milieu urbain ont pu être calculées à partir de facteurs environnementaux tels que la densité de maisons en briques ou l'absence de réseau de collecte des ordures en Thaïlande (Thammapalo et al, 2008). Les corrélations entre des données sociodémographiques (éducation, revenu, taille du ménage) et des données épidémiologiques ont permis d'identifier les populations les plus vulnérables au Brésil (De Mattos Almeida et al, 2007). L'intégration d'images satellites dans la chaîne de traitement permet d'identifier et de caractériser de manière automatique et à petite échelle les zones à risques vectoriels (Fuller et al, 2010).…”
Section: Relationunclassified
“…1 As a result, some studies on these associations identified the occurrence of dengue fever in heterogeneous areas in terms of socioeconomic and environmental indicators.…”
Section: Introductionmentioning
confidence: 99%